Evaluation of single and multispecies probiotic applications for the prevention of Motile Aeromonads Septicaemia in gourami, Osphronemus gourami - Agista Tsani Untsa; Widanarni Widanarni; Sukenda Sukenda; Usamah Afiff; Munti Yuhana (Jurnal Akuakultur Indonesia)
The aim of this study was to evaluate single and multispecies probiotic applications for the prevention of Motile Aeromonads Septicaemia (MAS) disease in gourami, Osphronemus gourami. The experiment consisted of the in vitro inhibition test and the in vivo application of probiotics in gourami. The in vivo assay, consisted of five treatments and five replicates, namely: negative control (K-); positive control (K+); (B) fish fed with  supplementation of 1% (v/w) probiotic Bacillus NP5 RifR cells and challenged with Aeromonas hydrophila RifR; (L) fish fed with supplemention of probiotic Lactobacillus plantarum CipR 1% (v/w); challenged with A. hydrophila RifR; (BL) fish fed with mixture supplementation of Bacillus NP5 RifR 0.5% (v/w)+L. plantarum CipR 0.5%; infected with A. hydrophila RifR. Fish (29.57 ± 1.00 g) were reared in a 45 L volume aquaria with a rearing density of 10 fish/m3 for 50 days, with   feeding trial three times a day. The challenge test was conducted by intramuscular injection with pathogenic A. hydrophila RifR cells (106 CFU/mL) on day 41st. In vitro test results showed that single and multispecies probiotics significantly (P<0.05) inhibited A.hydrophila RifR. In vivo experiment showed that probiotic supplementation treatments improved the growth performance, and microbiota diversity in the gut.  The immune responses, fish resistance to A. hydrophila RifR and gourami survival rate in all treatments of supplemented feed were significantly higher compared to the positive control. The best treatment, multispecies probiotics significantly (P<0.05) improved the survival of gourami 96.67% post infection with A. hydrophila RifR.